Effectiveness of culture-based game exercises on cognitive function in older adults participating in gymnastics - Sudibjo, Prijo; Waluyo, Sumarni Djoko; Wara Kushartanti, Bernadetta Maria; Sutarni, Sri; Padli, (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to examine the effectiveness of culture-based game exercise training on the cognitive function of older adults. This study was a quasi-experimental research with a pre-test and post-test control design. The research subjects were 40 elderly individuals who are members of the Teratai elderly gymnastics group in the Nogotirto Gamping housing area, Sleman, Special Region of Yogyakarta, Indonesia. The research instruments included the Mini Mental State Examination (MMSE) to measure cognitive function, along with video recordings of physical exercise activities, recordings of culture-based game songs, and exercise props. After being given the intervention of culture-based game exercise training in the intervention group (IG), there was a significant improvement in cognitive function scores from pre-test to post-test (MMSE score: Fh;df=19; α=3.622; p=.003 < .05), and there was a significant difference in the change in MMSE scores between the intervention group (IG) and the control group (CG) (Fh;df=19; α=0.280; p = .004 < .05) with a large effect size (d=2.363). In the control group (CG), which engaged in daily activities such as singing culture-based game songs, cognitive function also improved, but the change was not statistically significant (p>.05). In conclusion, culture-based game exercise is effective in improving cognitive function in older adults.